Comparing Course Modalities for Religious Education Outcomes - Sweat, Anthony R. (Religious education, 2025)
This study statistically analyzes data from 241 university students in the same religion course during the same semester, with the same instructor, enrolled in four different course modalities: face-to-face, blended, synchronous online, and asynchronous online. Across modalities, students received identical course content and assessments. When statistically controlling for gender, incoming GPA, modality motivation, teacher rapport, and peer connectedness, data indicate no significant differences across modalities on overall course score, final exam, student course ratings, or religious outcomes. Implications of this research are analyzed and discussed, including limitations of specific circumstance, population homogeneity, and sample size.